Effectivity and adsorption mechanism of food waste biochar for triclosan removal: a spectroscopic and experimental approach - Kang, Jin Kyu; Seo, Eun Jin; Lee, Chang Gu; Moon, Joon Kwan; Park, Seong Jik (Biomass Conversion and Biorefinery, 2023)
Food waste from households and restaurants was pyrolyzed to food waste biochar (FWB), and it was used for triclosan (TCS) removal from aqueous solutions. Food waste thermally treated at 300 °C (FWB-300) showed higher adsorption potential than samples treated at higher temperatures (450–750 °C), because of its increased specific surface area and abundant functional groups for hydrogen bonding with TCS. X-ray photoelectron spectroscopy indicated that inorganic chlorine disappeared with the appearance of organic chlorine, and these changes were related to TCS adsorption on the FWB surface. Kinetic adsorption experiments demonstrated that the pseudo-nth-order model had a superior fit with strong initial adsorption behavior for TCS adsorption. The order of reaction (n) was 2.3 and 4.3 at the initial TCS concentrations of 5 and 50 mg/L, respectively. The Langmuir isotherm model was the best fit for TCS adsorption, while the Redlich-Peterson model was equalized with the Langmuir model and the adsorption capacity was 35.6 mg/g. Thermodynamic studies of TCS adsorption revealed a spontaneous and exothermic reaction. The adsorption of TCS onto FWB-300 decreased slightly from 13.9 to 10.0 mg/g as the pH increased from 3 to 11. The impact of coexisting anions on TCS adsorption is in the following order: HPO42− > HCO3− > SO42− ≈ NO3−. It is concluded that FWB-300 can be used as an accessible and inexpensive adsorbent for the removal of TCS from an aqueous solution.
Keywords: Adsorption experiment; Adsorption mechanism; Adsorption potential; Biochar; Experimental approaches; Food waste; Highest temperature; Inorganics; Organic chlorine; Triclosan; Adsorption; Biochar; Food waste; Pyrolysis; Spectroscopy; Triclosan